High order sliding mode control for grid integration of photovoltaic systems - Ech-cherki, Noureddine; Echab, Oumaima; Errami, Youssef; Obbadi, Abdellatif; Sahnoun, Smail; Aoutoul, Mohssin (International Journal of Applied Power Engineering (IJAPE), 2025)
The article suggests employing second-order sliding mode control (SOSMC) to manage photovoltaic systems (PVS) connected to the electrical grid. These systems face complexities due to non-linearities, variability, uncertainties, disturbances, and climate changes. The proposed control strategy utilizes two converters: one at the photovoltaic generator (PVG) side for maximum power point tracking (MPPT) to optimize energy generation and another at the grid connection point to regulate power injection into the grid and maintain the DC bus voltage (Vdc) while achieving unit power factor (UPF). Both converters are equipped with SOSMC controllers, enabling independent adjustment of active (P) and reactive (Q) power. This approach aims to enhance the energy efficiency and robustness of PVS under varying climatic conditions. The performance of the system is evaluated under standard and variable irradiation conditions using the MATLAB/Simulink environment. Simulation results indicate that SOSMC significantly improves system performance and efficiency compared to conventional vector control (CVC). Notably, it reduces active power overshoot by 100%, decreases Vdc response time, and lowers total harmonic distortion (THD) of the current to 1.19%, demonstrating its effectiveness across different irradiation levels.